2012
DOI: 10.1080/07315724.2012.10720028
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Enteral Immunonutrition Containing Lactoferrin in Tube-Fed Bedridden Patients: Immunological and Nutritional Status

Abstract: Prem-8 did not demonstrate superiority to the control formula with respect to immunological and nutritional variables, whereas the body mass index of patients in the Prem-8 group marginally decreased. However, Prem-8 had a favorable effect on the incidence of fever in a subgroup of patients with low protein intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In adults, inflammation (IL-6) was attenuated when Lf was administered alone in doses of 200 mg/d in pregnant and nonpregnant females with iron homeostasis disorders ( 43 , 45–47 ), although doses of only 32 mg/d given in combination with whey protein were also effective in reducing CRP, TNF-α, and IL-6 in T2D ( 55 ). Lf doses >200 mg/d, given either alone or in combination with other compounds, were effective in reducing systemic inflammation outcomes in some ( 41 ), but not all ( 35 , 40 , 48 , 53 ), trials. Doses <200 mg/d were not effective in some combinations in adults ( 57 ) and children ( 54 ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In adults, inflammation (IL-6) was attenuated when Lf was administered alone in doses of 200 mg/d in pregnant and nonpregnant females with iron homeostasis disorders ( 43 , 45–47 ), although doses of only 32 mg/d given in combination with whey protein were also effective in reducing CRP, TNF-α, and IL-6 in T2D ( 55 ). Lf doses >200 mg/d, given either alone or in combination with other compounds, were effective in reducing systemic inflammation outcomes in some ( 41 ), but not all ( 35 , 40 , 48 , 53 ), trials. Doses <200 mg/d were not effective in some combinations in adults ( 57 ) and children ( 54 ).…”
Section: Resultsmentioning
confidence: 98%
“…Circulating TNF-α concentrations were measured in 3 trials, of which 2 trials (66%) reported a significant decrease and 1 trial (33%) reported no change. Decreased TNF-α was reported following bLf 250 mg/d for 180 d in healthy females ( 41 ), and WPI powder with bLf 32.4 mg/d for 3 mo in adults with T2D ( 55 ), whereas there was no difference in TNF-α following bLf 1000 mg/d for 12 wk in neurological patients ( 53 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Bovine milk-derived LF used in some clinical trials and the rhLFs expressed in yeast or transgenic plants are given orally because of the potential immunogenicity of parenteral administration. 12,13,[19][20][21] Amino acid sequence homology and sugar moiety have to be compatible with the human immune system. In fact, sugar moieties in LF play a crucial role in the interaction with the host's cell receptors.…”
Section: Introductionmentioning
confidence: 99%